(untitled) (Proceedings of the International Conference on Social Sciences, 2024)
Online teaching and learning are an appropriate alternative for sustained continuity, in case of interrupted learning by pandemics or crises. It has been faced with multiple challenges of dishonesty that has intensified due to technological advancement and the smartness of youth in technology. The focus of this paper is on the literature review analysis on the case of downloading and hacking of the exams that has become a norm with online examination administration. The objective of the paper is to investigate the incidence of downloading of answers with online invigilation measures available. It also seeks to confirm whether exams are hacked into prior to the examination hour and with what effects on the overall class performance. Literature review analysis through desktop research was conducted by examining cross cutting publications on the topic. Special focus evolved around studies that were done from the pandemic in the year 2020 to date, when the unpreparedness for instructors was high and the tension with the learners so critical. Qualitative research was used in the study. It is assumed remotely that as the adjustment took place and instructors were equipped, things may have improved for the better. With standardized agreed upon technological interventions, instructors can help reduce the incidences of online academic dishonesty in examinations. Recommendations have been made to educate online instructors on the keenness required to achieve integrity in exam participation by learners who will in turn apply the same in life.